Evaluating Impacts of Micro-Architectural Metrics on Error Resilience and Performance of General Purpose Gpu Applications - Topçu, Burak; Topçu, Burak; Öz, Işıl (01. Izmir Institute of Technology, 2023)
Rapidly growing data processing tasks require powerful and energy-efficient heterogeneous computing systems, and GPUs take on a significant mission for those systems in accelerating heavy workloads by executing multiple parallel tasks concurrently. Increasing architectural complexity and widening employment of GPUs bring error resiliency concerns for safety-critical applications. Furthermore, approaches that enhance performance and reduce energy dissipation handle error resiliency on GPUs through approximate computing solutions. Evaluating error resiliency in terms of either identifying error proneness of a system or investigating approximations without much disturbing the output necessities robust knowledge about the execution of a program on a device. In this thesis, we develop a runtime performance and power monitoring tool visualizing the execution with detailed micro-architectural metrics. By utilizing the tool, we acquire several fundamental understandings about runtime performance bottlenecks and how perturbations affect output quality. Afterward, we propose a framework predicting fault vulnerability for error-resilient GPU applications. The framework can accurately estimate error tolerance and saves from analyzing the fault occurrence probability requiring significant effort. Depending on the performance bottlenecks observed with the tool and the error propagation gained during prediction experiments, we introduce a hardware-based approximation computing approach targeting to improve the performance and power of GPU programs, especially memory-bound ones. The approximation method, which resolves memory utilization bottlenecks at runtime, enhances performance by 1.49× (up to 2.1×) and diminishes energy consumption by 28.4% (up to 52.6%) while maintaining the accuracy on the output above 98%.

Hızla artan veri işleme görevleri güçlü ve enerji tüketimi açısından verimli heterojen hesaplama ortamları gerektirir ve GPU cihazları birçok görevi paralel şekilde çalıştırarak bu sistemlerdeki yoğun iş yüklerini hızlandırmada önemli bir misyon üstlenir. Artan mimari karmaşıklık ve GPU cihazlarının yaygın şekilde kullanılması güvenlik açısından önemli uygulamalar için hataya karşı dayanıklılığa ilişkin endişeler ortaya çıkarır. Yanı sıra, performansı artırırken enerji tüketimini azaltmayı hedefleyen yaklaşımlar ise hataya karşı dayanıklılığı yakınsamalar yapmak ve faydalanmak yönüyle konuyu ele alır. Hataya karşı dayanıklılığı, hata oluşumuna yönelimi veya çıktıyı çok bozmayacak yakınsamaları değerlendirmek bir programın cihazdaki çalışmasına yönelik kapsamlı bilgilere sahip olmayı gerekli kılar. Bu tezde, GPU'daki gerçek zamanlı çalışmayı mikro mimari ölçümler aracılığıyla sunan ve görselleştiren bir performans ve güç izleme aracı geliştirdik. Bu araç sayesinde, çalışma esnasındaki performans darboğazları ve meydana gelen hataların çıktı kalitesini nasıl etkilediği hakkında birçok temel anlayış elde ettik. Daha sonra, GPU uygulamaları için hata güvenlik açığını tahmin eden bir yapı öneriyoruz. Bu yapı, hata toleransını doğru bir şekilde tahmin etmeyi sağlar ve önemli çaba gerektiren hata oluşma olasılığını analiz etmekten kurtarır. İzleme aracıyla gözlemlenen performans darboğazları ve tahmin deneyleri sırasında elde edilen hata yayılımı gözlemlerini temel alarak, özellikle bellek kullanımından kaynaklı GPU programlarının performansını ve gücünü iyileştirmeyi hedefleyen donanım tabanlı bir yakınsama aracı sunuyoruz. Çalışma zamanında bellek kullanımına yönelik darboğazlarını çözen yakınsama yöntemi çıktıdaki doğruluğu %98'in üzerinde tutarken, performansı 1,49× (en fazla 2,1×) artırır ve enerji tüketimini %28,4 (%52,6'ya kadar) azaltır.
Mikro-mimari Metriklerin Genel Amaçlı Gpu Uygulama Hatalarına ve Performansına Etkilerinin Değerlendirilmesi
Thesis (Master)--İzmir Institute of Technology, Computer Engineering, Izmir, 2023
Includes bibliographical references (leaves. 88-99)
Text in English; Abstract: Turkish and English
Keywords: GPU applications; Micro-architectural metrics; Error resilience; CUDA